Two copies of constitution of the Irish Republican Brotherhood, titled 'Constitution as revised to date 1920', issued "By order of the Supreme Council", with addenda, September 1919, - Irish Republican Brotherhood (1919)
Covers stamped "B 176" and "B 186". B 186 has inserted photostat copy of ‘Addenda to Constitution, September, 1919’ endorsed as a true copy by Vivion de Valera, with note regarding original copy (MS 31,233/1), 19 March 1964.